United States, Iñupiat woman holding child in Utqiaġvik - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
Native woman picking up child in fur hood. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3